Perancangan Alat Reaktor Alir Pipa Vertikal (Plug Flow Reactor) dengan Buffle Untuk Pembuatan Biodiesel Secara Kontinyu dengan Perubahan Laju Alir Reaktan - Muhammad Guntur; Ayu Chandra Kartika Fitri (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2020)
Biodiesel is fuel for diesel engines consisting of alkyl esters of fatty acids. Biodiesel is made by reacting vegetable oil with alcohol through trans-esterification reaction with a compound catalyst esters with glycerol by-product. In studies conducted using a production process of continuous reactors(Plug Flow Reactor) which has been designed in which the process of mixing and stirring among the main biodiesel feedstock with the catalyst takes place continuously with specific time and temperature. Inside the reactor are designed with a baffle. Baffle serves to expand the contact surface, set the flow through the shell so that the high turbulence will be obtained, and prevent the occurrence of vibration on the tube. To test the tool that was created to do research with kapok oil feedstock is reacted with methanol and base catalyst(KOH). Variables given is flow rate 150ml/minute, 200ml/minute, and 250ml/minute. Characteristics of kapok oil is produced at a variable mol ratio of 6:1methanol to oil mol and amount of catalyst 1 % and feed 250 ml/minute namely:% FAME 95.70 %